Event-Related Potential Measures of Attention Capture in Adolescent Inpatients With Acute Suicidal Behavior - Tavakoli, Paniz; Boafo, Addo; Dale, Allyson; Robillard, Rebecca; Greenham, Stephanie L.; Campbell, Kenneth (Frontiers in Psychiatry, 2018)
Impaired executive functions, modulated by the frontal lobes, have been suggested to be associated with suicidal behavior. The present study examines one of these executive functions, attentional control, maintaining attention to the task-at-hand. A group of inpatient adolescents with acute suicidal behaviour and healthy controls were studied using a passively presented auditory optimal paradigm. This “optimal” paradigm consisted of a series of frequently presented homogenous pure tone “standards” and different “deviants”, constructed by changing one or more features of the standard. The optimal paradigm has been shown to be a more time-efficient replacement to the traditional oddball paradigm, which makes it suitable for use in clinical populations. The extent of processing of these “to-be-ignored” auditory stimuli was measured by recording event-related potentials (ERPs). The P3a ERP component is thought to reflect processes associated with the capturing of attention. Rare and novel stimuli may result in an executive decision to switch attention away from the current cognitive task and toward a probe of the potentially more relevant “interrupting” auditory input. On the other hand, stimuli that are quite similar to the standard should not elicit P3a. The P3a has been shown to be larger in immature brains in early compared to later adolescence. An overall enhanced P3a was observed in the suicidal group. The P3a was larger in this group for both the environmental sound and white noise deviants, although only the environmental sound P3a attained significance. Other deviants representing only a small change from the standard did not elicit a P3a in healthy controls. They did elicit a small P3a in the suicidal group. These findings suggest a lowered threshold for the triggering of the involuntary switch of attention in these patients, which may play a role in their reported distractibility. The enhanced P3a is also suggestive of an immature frontal central executive, and may provide a promising marker for early identification of some of the risk factors for some of the cognitive difficulties linked to suicidality.